LigaSure Hemorrhoidectomy for Symptomatic Hemorrhoids: First Pediatric Experience - Grossmann, Ole; Soccorso, Giampiero; Murthi, Govind (European Journal of Pediatric Surgery, 2015)
Hemorrhoids are uncommon in children. Third and fourth degree symptomatic hemorrhoids may be surgically excised. We describe the first experience of using LigaSure (Covidien, Mansfield, Massachusetts, United States) to perform hemorrhoidectomies in children. LigaSure hemorrhoidectomy has been well described in adults and is found to be superior in patient tolerance as compared with conventional hemorrhoidectomy.
Keywords: symptomatic hemorrhoids; children; LigaSure; hemorrhoidectomy